2016
DOI: 10.1093/ajcp/aqw030
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Expression Is an Independent Prognosticator in FIGO Stage I Uterine Leiomyosarcoma

Abstract: Hormone receptor expression is not informative of outcome in the analysis of uterine sarcomas of all stages and histologic types. PR expression identifies patients with longer survival in stage I leiomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
5
17
3
Order By: Relevance
“…The mitotic index has been a significant prognostic parameter for LMS in some studies, but we found no significant association with outcome. This may be related to variables such as microscopic field diameters, counting methodology, cutoff points, and inaccuracy related to the presence of karyorrhectic nuclei.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The mitotic index has been a significant prognostic parameter for LMS in some studies, but we found no significant association with outcome. This may be related to variables such as microscopic field diameters, counting methodology, cutoff points, and inaccuracy related to the presence of karyorrhectic nuclei.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, we believe that PHH3 has the potential to be a valuable additional prognosticator for stage I tumours. Similar observations have been made for the use of steroid hormone receptor expression in stage I LMS …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…9,28Y30 In LMS, higher mitotic rate and coagulative necrosis have been associated with lower survival, whereas higher ER or PR expression is associated with decreased risk of recurrence. 28,29 In our study, the highest mitotic rate (mean = 24/10 HPF) was observed in the conventional surgery group, but this group also had the highest expression of ER (64%) and PR (50%) when compared with the other groups. In ESS, mitotic rate has been considered the strongest prognostic factor.…”
Section: Discussionsupporting
confidence: 42%
“…Although the positivity of estrogen and progesterone receptors is considered to be an important feature for the diagnosis of uterine malignancy, [14] the mitotic activity was not evaluated on the lung specimen leading to the wrong diagnosis oh leiomyosarcoma initially. After pelvic surgery, due to the estrogen and progesterone positive receptors status of the lung nodules, we decided to use megestrol, according to previous experience.…”
Section: [9]mentioning
confidence: 99%